The willingness to sell personal data - Volker Benndorf; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We elicit the willingness to sell personal data (contact information, Facebook details, preferences) in laboratory experiments, using a BDM and take-it-or-leave-it offers. Our experiments are novel in that (i) the experiments are incentivized, (ii) the focus on privacy issues is salient, and (iii) the use of the data - marketing purposes - is transparent and unambiguous. We find that only a minority of about 10% to 20% of the participants are unwilling to sell personal data, a share which is roughly constant across both the type of personal data and elicitation method. Subjects willing to sell request about exteuro 15 for their contact details and exteuro 19 for Facebook details.
Keywords: C90; C91; C81; 330; privacy; preference elicitation; valuation of personal data